Buffy coat signatures of breast cancer risk in a prospective cohort study - Chung, Felicia Fei Lei *; Maldonado, Sandra Gonzalez; Nemc, Amelie; Bouaoun, Liacine; Cahais, Vincent; Cuenin, Cyrille; Salle, Aurelie; Johnson, Theron; Erguner, Bekir; Laplana, Marina; Datlinger, Paul; Jeschke, Jana; et al. (BMC, 2023)
Background: Epigenetic alterations are a near-universal feature of human malignancy and have been detected in malignant cells as well as in easily accessible specimens such as blood and urine. These findings offer promising applications in cancer detection, subtyping, and treatment monitoring. However, much of the current evidence is based on findings in retrospective studies and may reflect epigenetic patterns that have already been influenced by the onset of the disease.